(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze the sociodemographic, clinical and economic aspects related to hospitalizations for mental and behavioral disorders in Minas Gerais from 2011 to 2020. This is a retrospective, descriptive, quantitative, of documentary base study with comparative statistical analysis. Data were obtained from the SUS Hospital Information System (SIH/SUS), by the SUS Informatics Department (DATASUS). There was a total of 179.252 hospitalizations, ranging from 14.030 to 24.146 cases yearly, an average of 17.925 cases per year. The mortality rate increased in this period (121,28%), an average of 0,75% per year. There were higher numbers of hospitalizations in the Center (27,1%) and Southeast (18%) regions, however, higher mortality rates were observed in the East (3,36%) and Northeast (3,16%). The highest frequency of hospitalizations occurred due to schizophrenia, schizotypal and delusional disorders (32.95%) and the highest mortality rate for dementia (13.35%). Disorders were predominant in males patients (64,36%), between 30-39 years (25%), white and brown colors. The most hospitalizations were on an urgent character (80,65%), the highest average length for a hospital stay was for dementia (119,1 days). The highest costs of hospitalizations were for schizophrenia, schizotypal and delusional disorders (129.435.383,69 reais/50,66%) and the stress-related neurotic disorders the lowest (954.952,02 reais/0,37%). The mental health policies contribute to the individuals seek medical care and interventions early, improving quality of life and reducing the number of hospitalizations. Mainly the Schizophrenia, with the highest number of hospitalizations and hospital expenses, considered by the OMS as the main cause of years of life lived with disability.